Social justice framework for exploring the role of leaders in redressing school safety and orderliness: a case study of multiple deprived schools in Johannesburg - Adhola, Caroline Akoth (My University, 2020)
Injustices of school safety and orderliness have received significant attention in education, because of their greater impact on the quality of teaching and learning than any other correlate of school improvement. Elsewhere in Africa and other parts of the world, various studies have emphasised the relationship between multiple deprivation and safety and how the two fuse to affect learner performance. However, in South Africa, school safety as a basis of school improvement is an area that is still under-researched. Studies conducted on safety have mainly focused on the impact of school violence with little attention paid to the manner in which school leaders redress the injustices of safety and orderliness. Lack of research in this area is what motivated this study, which used Nancy Fraser’s theory of social justice to investigate how leaders in multiple deprived schools perceive and redressed injustices of safety and orderliness through redistribution, recognition and representation as a basis for school improvement. The study may seem broad, but I felt that safety within deprivation is a social justice issue that needs to be addressed if the performance of South African learners in international standardised tests are to be on par with the performance from countries at similar level of development. The study utilised an interpretive approach to give me a better understanding of the leaders’ perception of the injustices the schools experienced and the strategies they used to alleviate them. In addition, the study employed a single case study, where a total of three principals, six educators and nineteen learner representatives were purposively sampled for the study. Multiple methods, such as individual interviews, focus group interviews, observation and photographs, were utilised to generate rich data, which was analysed using thematic analysis. The findings showed that the leaders had a common understanding of what depressed safety and orderliness in their schools. The study established that the leaders redressed the injustices by enhancing behavioural, physical and psychological/emotional safety. However, the schools still experienced some challenges with policies and negative school climate which are discussed in detail Chapter Six. The major contribution of the study was to develop models that can be used to enhance school safety and orderliness. I therefore developed two models of school safety. The first-generation school safety model demonstrated how leaders are currently redressing safety and orderly and the challenges they face. The second-generation model of school safety and orderliness strategies showed how school safety strategies can be improved to enhance safety in schools. It is hoped that the model will be useful in helping school leaders, policymakers and other partners interested in promoting learners right to safety and orderliness.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand Johannesburg, in fulfilment of the requirements for the Degree of Doctor of Philosophy in Education Leadership and Policy, 2020